Determinants Of Occupational Fatigue On Nurses In The Intensive Department Of Pekanbaru Medical Center Hospital In 2022: Determinan Kelelahan Kerja Pada Perawat Bagian Rawat Inap Di Rumah Sakit Pekanbaru Medical Center Tahun 2022 - Rohmatu Alfiah; Zulmeliza Rasyid; Yessi Harnani; Aldiga Rienarti Abidin; Syukaisih Syukaisih (Badnur Medisa Group, 2022)
Work fatigue is a tired condition felt by someone which is also characterized by a decrease in work productivity, workers, especially nurses, are likely to be at risk of experiencing work fatigue. From the results of the initial survey it was found that nurses experienced work fatigue such as lack of adequate rest because they always had to control patients often, felt bored and bored, felt back pain, dizziness, difficulty controlling emotions, drowsiness, caused by workload, working period, and also work attitude. The purpose of this study was to determine the factors causing work fatigue in inpatient nurses at Pekanbaru Medical Hospital. This type of quantitative research with a cross sectional study design was carried out at Pekanbaru Medical Center Hospital in March-May 2022. The sample in this study were all inpatient nurses, as many as 60 respondents. The sampling technique used is the total sampling technique. The analysis used univariate and bivariate analysis. The results showed that P-Value < so that the factors related to work fatigue were workload (P = 0.006, OR = 6,500), years of service (P = 0.018, OR = 4,297) and work attitude (P = 0.020, OR = 4,030). From the results of the study, there are conclusions and suggestions, that there is a relationship between workload, work period and work attitude with work fatigue in inpatient nurses at Pekanbaru Medical Center Hospital in 2022. It is expected that nursing staff, especially those who work at Pekanbaru Medical Center Hospital to find out more about the signs and symptoms as well as the focus that affects the occurrence of work fatigue, so that later productivity and performance will be even better.